Pengaruh Kepemimpinan Terhadap Disiplin Kerja Pada Kantor Kecamatan Tehoru Kabupaten Maluku Tengah - Wael , Dewi; Simarmata, Ricardo Manarintar (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
This research aims to determine the influence of leadership on work discipline at the Tehoru District Office, Central Maluku Regency. Data testing was carried out with a questionnaire which was analyzed using statistical analysis such as: validity and reliability tests, with the help of SPSS version 27 for Windows. The research results show that the Coefficient of Determination (R) is 0.984 or around 98.4%. A value of 98.40% indicates that leadership (X) has an influence on work discipline (Y) of 98.40%, and another 1.60% is influenced by other factors not included in this research. Based on hypothesis testing with the calculated t test of 40.983 and ttable of 1.7011 so that tcount > ttable (16,483 > 1.7011) at α = 5%. So it can be concluded that the hypothesis which states